One‐Pot Process for Hydrodeoxygenation of Lignin to Alkanes Using Ru‐Based Bimetallic and Bifunctional Catalysts Supported on Zeolite Y. Issue 8 (16th March 2017) - Wang, Hongliang; Ruan, Hao; Feng, Maoqi; Qin, Yuling; Job, Heather; Luo, Langli; Wang, Chongmin; Engelhard, Mark H.; Kuhn, Erik; Chen, Xiaowen; Tucker, Melvin P.; Yang, Bin
Abstract: The synthesis of high‐efficiency and low‐cost catalysts for hydrodeoxygenation (HDO) of waste lignin to advanced biofuels is crucial for enhancing current biorefinery processes. Inexpensive transition metals, including Fe, Ni, Cu, and Zn, were severally co‐loaded with Ru on HY zeolite to form bimetallic and bifunctional catalysts. These catalysts were subsequently tested for HDO conversion of softwood lignin and several lignin model compounds. Results indicated that the inexpensive earth‐abundant metals could modulate the hydrogenolysis activity of Ru and decrease the yield of low‐molecular‐weight gaseous products. Among these catalysts, Ru‐Cu/HY showed the best HDO performance, affording the highest selectivity to hydrocarbon products. The improved catalytic performance of Ru‐Cu/HY was probably a result of the following three factors: (1) high total and strong acid sites, (2) good dispersion of metal species and limited segregation, and (3) high adsorption capacity for polar fractions, including hydroxyl groups and ether bonds. Moreover, all bifunctional catalysts proved to be superior over the combination catalysts of Ru/Al2 O3 and HY zeolite. Abstract : Lignin to advanced biofuels : High yields (26–32 wt %) of alkanes in jet fuel or diesel range are directly produced through aqueous‐phase hydrodeoxygenation (HDO) conversion of softwood lignin catalyzed by Ru‐based bimetallic catalysts supported on zeolite Y. These bimetallic and bifunctional catalysts show high efficiency compared with the combination catalysts Ru/Al2 O3 and HY zeolite.